Analysis of Community Satisfaction with Public Services at the Population and Civil Registration Office of Seluma Regency - Meirio Pratama; Neri Susanti; Nenden Restu Hidayah (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine public satisfaction with public services in the Seluma Regency Population and Civil Registration Service. The sample in this study was 100 respondents, namely the people of Seluma Regency. Data collection uses observation, interviews, questionnaires and documentation. The analysis method used is IKM in this study based on KEPMENPAN Number 4 of 2007 concerning Guidelines for Preparing Community Satisfaction Surveys. From the results of the study, it was found that the quality of service at the Seluma Regency Population and Civil Registry Office has met the expectations of customers or the community, in other words, the community is satisfied with the services provided by the Seluma Regency Population and Civil Registry Office office with the criteria